PENGARUH PENAMBAHAN BERBAGAI STARTER PADA PEMBUATAN SILASE TERHADAP KUALITAS FISIK DAN pH SILASE RANSUM BERBASIS LIMBAH PERTANIAN - Depo Kurniawan; Erwanto ,; Farida Fathul (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2015)
Objective of the research was to study the effect of using starter on silage making. Four treatments with 3 replications were applied in a completely randomized design. The treatments were R0 = Basal diet; R1 = R0 + EM-4 4%; R2 = R0 + enriched EM-4 4%; and R3 = R0 + rumen fluid 4%. Results of the experiment showed that EM-4, enriched EM-4, and rumen fluid significantly affect the color, texture, pH, as well as the smell of the silage. The best quality of silage was achieved by using EM-4 4% and using rumen fluid 4% as starter in silage making. Keywords: Em-4, Em-4 culture 4% , rumen liquid, silage, the physical quality of the Silage.